Distinção entre traficante e usuário: influência de fatores extrajurídicos no processo decisório judicial - Wormhoudt, Talitha Passos de Lima (2023)
The research aims to study how the Judiciary has framed the conduct of agents in the crime of drug trafficking and the elements used to differentiate dealer-user, seeking to identify whether and to what extent extra-legal factors affect the outcome of this decision. The research analyzes how Law nº 11.343/2006 (Drug Law) has been applied in the first instance in the Court of Justice of São Paulo, describing the reasoning of decisions in legal categories (those based on legal issues), jurisprudence (based on jurisprudence or doctrine) and extrajuridical (thus considered those that have no legal or jurisprudential basis). The work dialogues with studies that investigated the application of the drug law in Brazil, and uses the theoretical framework on judicial decision-making behavior. In empirical terms, 161 sentences handed down in the first instance in December 2019, from criminal courts in six municipalities of different sizes in the State of São Paulo, were analyzed. The main conclusion is that the use of factors classified in this research as extra-legal predominate in decisions, and their use is even more recurrent in decision-making for the conviction of defendants for trafficking.